An Algorithmic approach to improve Network Performance for 1G-EPON (International Journal of Engineering and Computer Science, 2015)
This paper proposes a novel ‘TD-sense algorithm’ for improve the network performance and compares it with a standard DBA_GATED algorithm. The algorithm is implemented by emulating an access network with the use of two 1G transceivers for 1G EPON. The algorithm is tested for Triple Play services that include simulated voice, video and data packets. The algorithm is found to maintain a better tradeoff between throughput and delay, than the existing DBA_GATED algorithm